STRATEGI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM UNTUK MENINGKATKAN PEMAHAMAN AKHLAK MULIA PADA SISWA SMA AL GHAZALI RAWA KALONG BOGOR - Mudzakir Mudzakir; Desmaliza Desmaliza; Fathudin Ali; Kamil Falahi (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
This study aims to describe the Islamic Religious Education (PAI) learning strategy in improving the understanding of noble morals in Al Ghazali Rawa Kalong Bogor Senior High School students and examine the extent to which the strategy contributes to changes in students' knowledge, attitudes, and behavior. The type of research used is qualitative research with a descriptive approach, through data collection techniques in the form of observation, interviews, and documentation of PAI teachers, students, and school religious activities. The results of the study indicate that the PAI learning strategy at Al Ghazali Rawa Kalong Bogor Senior High School is implemented in an integrated manner through exemplary behavior (uswah hasanah), habituation, advice and mau'izhah hasanah, contextual and interactive learning in the classroom, and reinforcement through school religious activities such as congregational prayer, Al-Qur'an recitation, commemoration of Islamic holidays, and Islamic spiritual activities. These strategies have a positive effect on improving students' understanding of noble morals, which is evident from students' ability to explain concepts and examples of commendable morals, increased awareness of worship, and improvements in discipline, politeness, and social awareness, although several obstacles are still encountered such as the influence of the environment outside the school, social media, and variations in student learning motivation.